2006
DOI: 10.1111/j.1467-9361.2005.00306.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative Deprivation, Wage Differentials and Mexican Migration

Abstract: This paper constructs and tests a model that incorporates relative deprivation into the migration decision. Relatively deprived individuals view their situations as less than a community standard. Another innovation of this paper is the utilization of a cluster approach to wage differentials. This cluster method takes account of individual characteristics while avoiding the severe multicollinearity problems inherent in the standard wage equation approach. Using data from the Mexican Migration Project, relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(81 citation statements)
references
References 15 publications
5
72
0
4
Order By: Relevance
“…The micro studies begin with Taylor (1989, 1991), who find a positive association between purely relative deprivation and emigration from a small part of rural Mexico, just as Bhandari (2004) and Quinn (2006) find in other settings. Reversing the direction of causation, McKenzie and Rapoport (2007) find that migration tends to reduce inequality in Mexico.…”
Section: Inequality and Migrationmentioning
confidence: 99%
See 2 more Smart Citations
“…The micro studies begin with Taylor (1989, 1991), who find a positive association between purely relative deprivation and emigration from a small part of rural Mexico, just as Bhandari (2004) and Quinn (2006) find in other settings. Reversing the direction of causation, McKenzie and Rapoport (2007) find that migration tends to reduce inequality in Mexico.…”
Section: Inequality and Migrationmentioning
confidence: 99%
“…Finally, two of the micro studies investigate the association between exclusively relative economic resources and migration, finding that lower migration rates are associated with greater relative access to land in Nepal (Bhandari 2004) and higher relative wages in Mexico (Quinn 2006). But these studies control for absolute measures of assets (e.g.…”
Section: Micro Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…the perception of an individual or household to be worse o or disadvantaged compared to a particular reference group, for example, other people in the same village (Quinn, 2006, Stark and Taylor, 1989, 1991. Quinn (2006) uses the data from the Mexican Migration…”
Section: Literature Reviewmentioning
confidence: 99%
“…) One branch of this body of research has dealt with migration. Several studies have shown empirically that a concern for relative deprivation impacts significantly on migration outcomes (Stark and Taylor 1989;Stark and Taylor 1991;Quinn 2006;Stark et al 2009). Theoretical expositions have shown how the very decision to resort to migration and the choice of migration destination (Stark 1984;Stark and Yitzhaki 1988;Stark and Wang 2007;Stark and Fan 2011;Fan and Stark 2011), as well as the assimilation behavior of migrants (Fan and Stark 2007), are modified by a distaste for relative deprivation.…”
Section: Why a Merger Of Populations Without Marriages Increases Unhamentioning
confidence: 99%